Systems approaches to managing change: a practical guide. - Reynolds, Martin; Holwell, Sue (Springer, 2010)
In a world of increasing complexity, instant information availability and constant flux, systems approaches provide the opportunity of a tangible anchor of purpose and iterate learning. The five approaches outlined in the book offer a range of interchangeable tools with rigorous frameworks of application tried and tested in the ‘real world’. The frameworks of each approach form a powerful toolkit to explore the dynamics of how societies emerge, how organisations create viability, how to facilitate chains of argument through causal mapping, how to embrace a multiplicity of perspectives identifying purposeful activity and how to look for the bigger picture across multiple disciplines. Systems Approaches offers an excellent first introduction for those seeking to understand what ‘systems thinking’ is all about as well as why the tools discussed herein should be applied to management and professional practice. This book provides a practical guide, and the chapters stand alone in explaining and developing each approach -- Présentation de l'éditeur.